Association between infants’ serum levels of 26 metals and gut microbiota: a hospital-based cross-sectional study in China - Yan, Xing; Qiu, Jun; Huang, Ruiwen; Peng, Xiaoming; Xiang, Shi-ting; Zhao, Kunyan; Peng, Yunlong; Zhuang, Yan; Ma, Ye; Wu, Mingyang; Yang, Fei (Frontiers in Microbiology, 2025)
BackgroundThis study examined the associations of toxic metals, essential metals, and rare earth elements with infant gut microbiota at Hunan Children’s Hospital, China.MethodsGeneralized linear regression (GLR) was used to assess individual metal associations with alpha diversity, whereas Bayesian kernel machine regression (BKMR) and weighted quantile sum (WQS) regression were applied to evaluate metal mixture-taxa relationships.ResultsResults showed that barium (Ba) and arsenic (As) were positively associated with the Chao1 index, whereas chromium (Cr), antimony (Sb), tungsten (W), cobalt (Co), copper (Cu), lanthanum (La), praseodymium (Pr), and uranium (U) showed negative associations. Six antagonistic interactions were identified: Cr-W (β = −2.57), Cr-La (β = −3.82), Tl-As (β = −4.48), As-La (β = −4.31), As-Pr (β = −5.85), and La-Pr (β = −2.38). Two synergistic interactions were observed: Sb-Pr (β = 2.17) and Sb-U (β = 2.14). BKMR analysis identified Mn as a key contributor to Burkholderia-Caballeronia-Paraburkholderia abundance (PIP = 0.535). Metal mixture exposure was positively linked to Ralstonia abundance, with As having the highest contribution (PIP = 0.886). Cu was the primary driver of Clostridium_ sensu_stricto_1 abundance (PIP = 0.867), with synergistic Mn-Cu (β = 0.797) and Ba-Cu (β = 0.720) interactions.DiscussionThese findings demonstrate that As and Cu are the most influential metals on gut microbial alpha diversity, whereas Cu, As, and Mn significantly influence specific microbial taxa, providing novel epidemiological evidence on metal-gut microbiota interactions in vulnerable infants.